2022
DOI: 10.3390/ijms232012582
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of JAK2 46/1 Haplotype in the Predisposition to Myeloproliferative Neoplasms

Abstract: Haplotype 46/1 (GGCC) consists of a set of genetic variations distributed along chromosome 9p.24.1, which extend from the Janus Kinase 2 gene to Insulin like 4. Marked by four jointly inherited variants (rs3780367, rs10974944, rs12343867, and rs1159782), this haplotype has a strong association with the development of BCR-ABL1-negative myeloproliferative neoplasms (MPNs) because it precedes the acquisition of the JAK2V617F variant, a common genetic alteration in individuals with these hematological malignancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 138 publications
3
5
0
Order By: Relevance
“…In the literature, the germline haplotype 46/1, identi ed by the rs10974944 (C > G) variant, has a well-documented association with JAK2 V617F 14,[37][38][39] as also observed in our study. The high frequency of the G allele of rs10974944 in individuals positive for JAK2 V617F contributes to discussions about the non-random correlation between these two genetic alterations 13,40 This relationship is in line with another nding from our study, haplotype 2 (rs10974944G/rs10815151C/rs1011004A/rs77375493T), which strengthens concepts based on the interaction between rs10974944 (C > G) and JAK2 V617F (rs77375493 -G > T). These propositions are in agreement with ndings involving haplotype 46/1 in other Brazilian, Taiwanese, European, Chinese, and Japanese populations 16,[32][33][34]41 , indicating that the possible mechanisms preceding the acquisition of JAK2 V617F are not limited to a speci c ethnic group; therefore, its evolutionary basis can be considered as a genetic predisposition factor for the disease 8 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the literature, the germline haplotype 46/1, identi ed by the rs10974944 (C > G) variant, has a well-documented association with JAK2 V617F 14,[37][38][39] as also observed in our study. The high frequency of the G allele of rs10974944 in individuals positive for JAK2 V617F contributes to discussions about the non-random correlation between these two genetic alterations 13,40 This relationship is in line with another nding from our study, haplotype 2 (rs10974944G/rs10815151C/rs1011004A/rs77375493T), which strengthens concepts based on the interaction between rs10974944 (C > G) and JAK2 V617F (rs77375493 -G > T). These propositions are in agreement with ndings involving haplotype 46/1 in other Brazilian, Taiwanese, European, Chinese, and Japanese populations 16,[32][33][34]41 , indicating that the possible mechanisms preceding the acquisition of JAK2 V617F are not limited to a speci c ethnic group; therefore, its evolutionary basis can be considered as a genetic predisposition factor for the disease 8 .…”
Section: Discussionsupporting
confidence: 90%
“…Studies indicate that this genetic alteration is a factor that favors the acquisition of JAK2 V617F by increasing the mutational rate of JAK2, which can lead to DNA damage and replication errors [7][8][9] . In addition to being identi ed in MPN patients of various populations, this haplotype has also been associated with more pronounced alterations in laboratory exams, presence of splenomegaly, in ammatory dysregulation, familial cases of MPNs (increasing the risk of developing any myeloproliferative neoplasm by 5 to 7 times) and abnormal methylation of the gene promoter [10][11][12][13] . Therefore, the JAK2 46/1 haplotype confers predisposition to the development of myeloproliferative neoplasms associated with the JAK2 V617F mutation (OR = 3.7; 95% CI = 3.1-4.3) and provides a conceptual framework in which a constitutional genetic component is associated with a substantial increase in the risk of acquiring a speci c somatic mutation 14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the frequency of the 46/1 haplotype, associated with rs10974944 , has been linked to a higher prevalence in patients with myeloproliferative neoplasms, especially those harboring JAK2 V617F + . This association has been observed not only in other Brazilian populations as described by Macedo et al 16 but also in studies conducted across various populations worldwide, including Asian, European, and North American populations, as discussed in one of our previous integrative reviews 13 . Additionally, the ancestral contribution to the Brazilian population, particularly in the Amazon region, is characterized by a mixture of three main ethnic groups: Native Americans (NAM), Europeans (EUR), and Africans (AFR) 39 .…”
Section: Discussionsupporting
confidence: 70%
“…Studies indicate that this genetic alteration is a factor that favors the acquisition of JAK2 V617F by increasing the mutational rate of JAK2, which can lead to DNA damage and replication errors 7 9 . In addition to being identified in MPN patients of various populations, this haplotype has also been associated with more pronounced alterations in laboratory exams, presence of splenomegaly, inflammatory dysregulation, familial cases of MPNs (increasing the risk of developing any myeloproliferative neoplasm by 5 to 7 times) and abnormal methylation of the gene promoter 10 13 . Therefore, the JAK2 46/1 haplotype confers predisposition to the development of myeloproliferative neoplasms associated with the JAK2 V617F mutation (OR = 3.7; 95% CI = 3.1–4.3) and provides a conceptual framework in which a constitutional genetic component is associated with a substantial increase in the risk of acquiring a specific somatic mutation 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variants of the leptin and leptin receptor genes in cancer patients have been described in some studies and are associated with decreased risk of cancer susceptibility, smaller tumor size, less node and distant metastasis, and less distant metastasis [ 225 ], although other polymorphisms are related to an increase in tumorigenesis [ 226 ]. The leptin signaling cascade can be involved in changes in susceptibility to cancer processes and it has been suggested that genetic variations in JAK2 are involved in the generation of several signs of myeloproliferative neoplasms [ 227 ], as well as SOCS3 polymorphisms, that may favor the progression towards liver fibrosis and hepatocellular carcinoma [ 228 ]. Hypermethylation of SOCS3 has been reported to contribute to hepatocellular carcinoma development and progression [ 229 ].…”
Section: Functionality Of Leptin and Its Involvement In Pathologymentioning
confidence: 99%